(untitled) (Al-Aasar, 2025)
Indeed, Allah Almighty has brought forth within this Islamic Ummah eminent and great scholars who undertook the task of authoring works on the interpretation of the Noble Qur’an and teaching it. Among these noble scholars is Imam Muhammad al-Tahir ibn ‘Ashur (may Allah have mercy on him), who is considered one of the most prominent scholars who made significant contributions in this field. He devoted himself to authoring works that contain many issues related to da‘wah (Islamic preaching), the caller (da‘i), and the audience (mad‘u). Among the most important of these works is the tafsir al-Tahrir wa al-Tanwir, which is regarded as one of Ibn ‘Ashur’s most famous writings and through which he gained widespread recognition. This article is divided into an introduction defining the topic and explaining its importance, followed by two chapters. The first chapter includes a biography of the author, while the second chapter deals with the da‘wah-related issues concerning da‘wah itself, the preacher, and the audience, along with examples of these aspects. The purpose of this study is to introduce the life of the author and to clarify the da‘wah methodology of the book al-Tahrir wa al-Tanwir and its scholarly importance.